PELATIHAN MENDELEY SEBAGAI SOFTWARE MANAJEMEN REFERENSI BAGI MAHASISWA EKONOMI SYARIAH - Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Community Service activities by providing Mendeley Software training to students of the Sharia Economics Study Program at the Tarbiyatut Tholabah Lamongan Islamic Institute to be able to provide knowledge and practice in making lecture assignments such as papers and final assignments such as theses. This community service is entitled Mendeley Training as Reference Management Software for Sharia Economics Students. With the aim that Sharia Economics at the Tarbiyatut Tholabah Lamongan Islamic Institute can have an understanding and can practice directly. The method used is lecture, discussion and practice. The results showed that students who previously did not know became aware and were able to practice the use of Mendeley Software in their paper assignments and would later be used in final assignments or articles that would be published with automatic application in citation and reference lists.